Puccini's operas : the glorious dozen - Puccini, Giacomo, 1858-1924; Fisher, Burton D. (Opera classics library., 2004)
A comprehensive guide to Puccini's 12 operas, featuring insightful and in depth Commentary and Analysis, Story Narratives with over 120 Music Highlight Examples, and a newly translated Libretto of each opera (exclusing Turandot) with Italian English side-by-side.